Alcohol promotes renal fibrosis by activating Nox2/4-mediated DNA methylation of Smad7. (23rd January 2020) - Yang, Qin; Chen, Hai-Yong; Wang, Jia-nan; Han, Huai-Qin; Jiang, Ling; Wu, Wei-Feng; Wei, Biao; Gao, Li; Ma, Qiu-ying; Liu, Xue-qi; Chen, Qi; Wen, Jia-gen; et al.
Abstract: Alcohol consumption causes renal injury and compromises kidney function. The underlying mechanism of the alcoholic kidney disease remains largely unknown. In the present study, an alcoholic renal fibrosis animal model was first employed which mice received liquid diet containing alcohol for 4 to 12 weeks. The Masson's Trichrome staining analysis showed that kidney fibrosis increased at week 8 and 12 in the animal model that was further confirmed by albumin assay, Western blot, immunostaining and real-time PCR of fibrotic indexes (collagen I and α-SMA). In vitro analysis also confirmed that alcohol significantly induced fibrotic response (collagen I and α-SMA) in HK2 tubular epithelial cells. Importantly, both in vivo and in vitro studies showed alcohol treatments decreased Smad7 and activated Smad3. We further determined how the alcohol affected the balance of Smad7 (inhibitory Smad) and Smad3 (regulatory Smad). Genome-wide methylation sequencing showed an increased DNA methylation of many genes and bisulfite sequencing analysis showed an increased DNA methylation of Smad7 after alcohol ingestion. We also found DNA methylation of Smad7 was mediated by DNMT1 in ethyl alcohol (EtOH)-treated HK2 cells. Knockdown of Nox2 or Nox4 decreased DNMT1 and rebalanced Smad7/Smad3 axis, and thereby relieved EtOH-induced fibrotic response. The inhibition of reactive oxygen species by the intraperitoneal injection of apocynin attenuated renal fibrosis and restored renal function in the alcoholic mice. Collectively, we established novel in vivo and in vitro alcoholic kidney fibrosis models and found that alcohol induces renal fibrosis by activating oxidative stress-induced DNA methylation of Smad7. Suppression of Nox-mediated oxidative stress may be a potential therapy for long-term alcohol abuse-induced kidney fibrosis.